2019
DOI: 10.1016/j.jgg.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-S6K1 pathway mediates cytoophidium assembly

Abstract: CTP synthase (CTPS), the rate-limiting enzyme in de novo CTP biosynthesis, has been demonstrated to assemble into evolutionarily conserved filamentous structures, termed cytoophidia, in Drosophila , bacteria, yeast and mammalian cells. However, the regulation and function of the cytoophidium remain elusive. Here, we provide evidence that the mechanistic target of rapamycin (mTOR) pathway controls cytoophidium assembly in mammalian and Drosophila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…1, D and E ). In agreement with our data, it has been demonstrated that rapamycin only mildly reduces the growth rate in fission yeast cells, whereas TORC1 activation is significantly inhibited (5658), as is in mammalian cells treated with rapamycin (51).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1, D and E ). In agreement with our data, it has been demonstrated that rapamycin only mildly reduces the growth rate in fission yeast cells, whereas TORC1 activation is significantly inhibited (5658), as is in mammalian cells treated with rapamycin (51).…”
Section: Resultssupporting
confidence: 92%
“…Drug inhibition of TOR signaling has been shown to reduce cytoophidium formation in mammalian cells (51). To test whether the same is true for fission yeast, we utilized everolimus and rapamycin, two well-established allosteric inhibitors of TORC1 pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mTOR has also been implicated in CTPS filament formation in Drosophila ( Aughey et al. , 2014 ; Sun and Liu, 2019 ). In Drosophila ovaries, CTPS filament assembly is regulated by Myc and activated cdc42-associated kinase (Ack; Strochlic et al.…”
Section: Introductionmentioning
confidence: 99%